Analisis Peran Pengalaman Kerja dan Linearitas Background Pendidikan terhadap Produktivitas Kerja Karyawan Work From Anywhere - Muhammad Faisal Shabri; Diah Priharsari; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Amid the â€œnew normalâ€ period after the receding of the Covid-19 pandemic and the change in the Work From Home (WFH) work system to Work From Anywhere (WFA). Every company must be able to maximize every element they have in order to survive, such as the productivity of their WFA employee. This research goal was to analyze the role of work experience and the educational background linearity of a WFA employee on his productivity using a mixed method. Techniques in qualitative methods are semi-structured interviews involving 10 informants processed using thematic analysis methods. While the quantitative method will use a questionnaire technique that gets 138 respondents. In qualitative data analysis, work experience has a role in the productivity of a WFA employee in terms of ease of adaptation. Meanwhile, it was found that employees with non-linear education directly would not have problems with their productivity as long as these employees were able to make up for their lack of knowledge. It is confirmed in the quantitative method, where there was a significant difference in average productivity between group levels of work experience of WFA employees and no significant difference in average productivity between linear and non-linear WFA employees.